Influenza A virus‐induced thymus atrophy differentially affects dynamics of conventional and regulatory T‐cell development in mice. Issue 5 (17th March 2021) - Elfaki, Yassin; Robert, Philippe A.; Binz, Christoph; Falk, Christine S.; Bruder, Dunja; Prinz, Immo; Floess, Stefan; Meyer‐Hermann, Michael; Huehn, Jochen
Abstract: Foxp3 + Treg cells, which are crucial for maintenance of self‐tolerance, mainly develop within the thymus, where they arise from CD25 + Foxp3 – or CD25 – Foxp3 + Treg cell precursors. Although it is known that infections can cause transient thymic involution, the impact of infection‐induced thymus atrophy on thymic Treg (tTreg) cell development is unknown. Here, we infected mice with influenza A virus (IAV) and studied thymocyte population dynamics post infection. IAV infection caused a massive, but transient thymic involution, dominated by a loss of CD4 + CD8 + double‐positive (DP) thymocytes, which was accompanied by a significant increase in the frequency of CD25 + Foxp3 + tTreg cells. Differential apoptosis susceptibility could be experimentally excluded as a reason for the relative tTreg cell increase, and mathematical modeling suggested that enhanced tTreg cell generation cannot explain the increased frequency of tTreg cells. Yet, an increased death of DP thymocytes and augmented exit of single‐positive (SP) thymocytes was suggested to be causative. Interestingly, IAV‐induced thymus atrophy resulted in a significantly reduced T‐cell receptor (TCR) repertoire diversity of newly produced tTreg cells. Taken together, IAV‐induced thymus atrophy is substantially altering the dynamics of major thymocyte populations, finally resulting in a relative increase of tTreg cells with an altered TCR repertoire. Abstract : Influenza A virus infection‐induced thymus atrophy is accompanied by a significant increase in the frequency of tTreg cells with an altered TCR repertoire, resulting from substantially altered dynamics of major thymocyte populations, namely an increased death of double‐positive (DP) thymocytes and augmented exit of single‐positive (SP) thymocytes.